A video seafloor survey of epibenthic communities in the Pacific Arctic including Distributed Biological Observatory stations in the northern Bering and Chukchi seas. (April 2019) - Cooper, Lee W.; Guarinello, Marisa L.; Grebmeier, Jacqueline M.; Bayard, Alynne; Lovvorn, James R.; North, Christopher A.; Kolts, Jason M.
Abstract: Two separate efforts to characterize epibenthic communities in the northern Bering and Chukchi seas using video imagery from a drop camera system have now been completed. In the initial phase in 2008, we acquired video imagery from the USCGC Healy while drifting on station during the multidisciplinary Bering Sea Program and used cluster analysis and non-metric multidimensional scaling to identify epibenthic assemblage types and associated sediment characteristics based upon along-track epifaunal counts. We also quantified the areal density of easily recognizable organisms such as brittle stars ( Ophiura sp.) and sea stars, which were abundant and easily identified. While sampling was not extensive enough to rigorously compare the density of epifauna with trawling data available from prior years, our observations confirmed the characteristics of epifaunal communities sampled through much more labor-intensive trawling. Densities of epifauna that could be readily enumerated were of the same order of magnitude in both types of observations. During the second phase in 2016 and 2017 of video observations from the CCGS Sir Wilfrid Laurier, we improved the quality of imagery, and obtained seafloor video footage from each station in the internationally coordinated sampling grid in the Distributed Biological Observatory (DBO). This grid lies in the productive waters of the northern Bering and Chukchi seas. Quantitative analysis was not undertaken in this second phase, but the imagery confirms the presence of specific organismal community assemblages that can be related to environmental factors such as sediment grain size and water mass identity that are available from other project data collected during the Bering Sea and DBO projects. For example, sandier sediments typically had diverse epifaunal communities including filter feeders as significant community components. In muddier sediments, deposit feeders such as brittle stars predominated. All the second phase video footage has been posted in both abbreviated form on the video-sharing website youtube.com, and longer (10 min per station) versions are freely downloadable from a Google Drive server. Future videography may help identify changes in epibenthic diversity and community composition and could be successfully evaluated with crowd-sourced citizen science and/or more traditional scientific documentation.